2018
DOI: 10.1007/s00223-018-0411-7
|View full text |Cite
|
Sign up to set email alerts
|

HypoparaNet: A Database of Chronic Hypoparathyroidism Based on Expert Medical-Surgical Centers in Italy

Abstract: Hypoparathyroidism is a rare disease characterized by low serum calcium levels and absent or deficient parathyroid hormone level. Regarding the epidemiology of chronic hypoparathyroidism, there are limited data in Italy and worldwide. Therefore, the purpose of this study was to build a unique database of patients with chronic hypoparathyroidism, derived from the databases of 16 referral centers for endocrinological diseases, affiliated with the Italian Society of Endocrinology, and four centers for endocrine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 24 publications
10
27
0
Order By: Relevance
“…This is the first report of clinical presentations and treatment approaches in Russian patients with hypoparathyroidism referred to specialized care. The analysis has shown that the most frequent cause of hypoparathyroidism was neck surgery, which made middle-aged females the most common patients with hypoparathyroidism, as described in literature (3,5,7,8,10,11). Postsurgical hypoparathyroidism occurred after a total thyroidectomy in most cases, following by a parathyroidectomy and then a partial thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the first report of clinical presentations and treatment approaches in Russian patients with hypoparathyroidism referred to specialized care. The analysis has shown that the most frequent cause of hypoparathyroidism was neck surgery, which made middle-aged females the most common patients with hypoparathyroidism, as described in literature (3,5,7,8,10,11). Postsurgical hypoparathyroidism occurred after a total thyroidectomy in most cases, following by a parathyroidectomy and then a partial thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where this data were available, magnesium deficiency was confirmed in 50% of cases (magnesium levels below the reference range) and vitamin D deficiency in 37.5% of all cases (serum 25 hydroxyvitamin D concentration was under 30 ng/dL). Hypoparathyroidism is characterized by low bone metabolism, explaining why bone mineral density (BMD) is usually normal or higher than normal, except after a parathyroidectomy for PHPT (8,12,23,24). A DXA exam was carried out at baseline evaluation for half of the patients and showed normal to high values and a low bone turnover profile typical of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This project involved nine Italian referral centers for endocrine diseases, a liated with the Italian Society of Endocrinology (Società Italiana di Endocrinologia, S.I.E.) and involved in the "HypoparaNet" research group (HypoPT working group) (27,28).…”
Section: Methodsmentioning
confidence: 99%